Elastic light-scattering measurements of single biological cells in an optical trap - Doornbos, Richard M. P. (2013)
We have developed an instrument for determination of the angular light scattering of beads and biological cells. The instrument uses radiation pressure for levitation of particles inside a cuvette. The setup consists of two 780-nm diode lasers in a vertical double-beam trapping configuration. In the horizontal direction a weakly focused 633-nm probe beam is used to illuminate the trapped particle. One can detect scattered light over the range of from - 150 to 150 deg with an angular resolution of 0.9 deg using an avalanche photodiode. With this setup light scattering from polystyrene beads was measured, and the obtained scattering patterns were compared with theoretical scattering patterns from Lorenz-Mie theory. The results show that the setup is stable, gives reproducible patterns, and qualitatively agrees with the calculations. Trapping of biological cells is more difficult than trapping of beads, because smaller forces result from smaller refractive indices. We present an angular scattering pattern measured from a human lymphocyte measured from 20 to 60 deg.